1999
DOI: 10.1164/ajrccm.159.1.9801007
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Regular Inhaled Formoterol, Budesonide, and Placebo on Mucosal Inflammation and Clinical Indices in Mild Asthma

Abstract: The present study was designed to observe the effects of 8 wk of treatment with formoterol (Foradil) 24 microgram, budesonide 400 microgram, and matched placebo inhaled twice a day on inflammatory indices in the bronchial mucosa of 64 patients with mild atopic asthma. Biopsies were obtained at the start and 1 wk before stopping a 9-wk period of treatment, and inflammatory cell numbers were assessed in the submucosa and epithelium by immunohistochemistry. Regular formoterol significantly reduced the number of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 25 publications
6
53
1
2
Order By: Relevance
“…It is clear that b 2 -agonists, through elevations in cellular cAMP, can reduce recruitment and activity of some types of proinflammatory cells. Lavage/biopsy studies have documented that formoterol inhalation reduces the number of mast cells and eosinophils in the airways of asthmatics [19], and that salmeterol can decrease the neutrophil number [20]. These sustained in vivo effects exclude the possibility that there is a complete tachyphylaxis for this type of anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that b 2 -agonists, through elevations in cellular cAMP, can reduce recruitment and activity of some types of proinflammatory cells. Lavage/biopsy studies have documented that formoterol inhalation reduces the number of mast cells and eosinophils in the airways of asthmatics [19], and that salmeterol can decrease the neutrophil number [20]. These sustained in vivo effects exclude the possibility that there is a complete tachyphylaxis for this type of anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…In guinea-pig models, eosinophil influx into the lungs after challenge was inhibited by formoterol [11,16]. In humans, there is also evidence for direct inhibitory effects on mast cell and eosinophil infiltration in vivo after inhaled formoterol therapy [15]. This could be due, in part, to decreased expression of adhesion molecules by lung fibroblasts, thus contributing to the reduction in asthmatic inflammation.…”
Section: ±10mentioning
confidence: 99%
“…Some in vivo studies in humans show inhibitory effects of formoterol on the late asthmatic response (LAR), but do not show decreased eosinophil numbers in blood and sputum [13,14]. However, WALLIN et al [15] found a reduced number of submucosal eosinophils in patients with more severe airway inflammation after treatment with inhaled formoterol. In guinea-pigs, formoterol inhibits the LAR as well as the eosinophilic influx [16].…”
mentioning
confidence: 99%
“…A study of formoterol, another long-acting b 2 -agonist, in asthmatics, even demonstrated a reduction in the number of biopsy mast cells [13]. Moreover, addition of inhaled salmeterol to the treatment of asthmatics who continued to show symptoms despite current treatment with inhaled corticosteroids resulted in a reduction in airway tissue eosinophil number compared to using an increased dose of inhaled steroid alone [14].…”
mentioning
confidence: 99%